2010
DOI: 10.1002/j.0022-0337.2010.74.4.tb04886.x
|View full text |Cite
|
Sign up to set email alerts
|

Blogging in a Biostatistics and Research Design Graduate Dental Course: For Learning or Interaction?

Abstract: The use of the Internet in health professions education has markedly increased in recent years. There is a need to understand the methods used by students to benefit from Internet-based teaching methods, especially those initially designed to promote social interaction such as blogs. This study describes how students used a blog in a biostatistics and research design graduate dental course. The aims of the blog were to offer exercises to train students for the exam and to enhance interaction among students and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In fact, incorporating these technologies could increase student engagement. El Tantawi found that 60 percent of students and 80 percent of non‐native speakers of English were more comfortable writing posts or comments than speaking in class 23 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, incorporating these technologies could increase student engagement. El Tantawi found that 60 percent of students and 80 percent of non‐native speakers of English were more comfortable writing posts or comments than speaking in class 23 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…However, assessment of statistical knowledge of medical clinicians has shown minimal improvement during the past decades, suggesting that little is known about how to accomplish such improvement. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%